2022
DOI: 10.3390/ma15227923
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Concrete Reinforced with Date Palm Fibers

Abstract: In recent decades, researchers have begun to investigate innovative sustainable construction materials for the development of greener and more environmentally friendly infrastructures. The main purpose of this article is to investigate the possibility of employing date palm tree waste as a natural fiber alternative for conventional steel and polypropylene fibers (PPFs) in concrete. Date palm fibers are a common agricultural waste in Middle Eastern nations, particularly Saudi Arabia. As a result, this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The physical properties of PPF were given by the supplier, as shown in Table 5. Frontiers in Materials frontiersin.org 2.1.3.3 Date palm fibres DPFs were obtained from 15-to 25-year-old date palm trees in and around Najran, Saudi Arabia (Althoey et al, 2022a). These trees constitute one of the most accessible diversities and are responsible for a significant volume of agro-waste.…”
Section: Polypropylene Fibres (Ppfs)mentioning
confidence: 99%
“…The physical properties of PPF were given by the supplier, as shown in Table 5. Frontiers in Materials frontiersin.org 2.1.3.3 Date palm fibres DPFs were obtained from 15-to 25-year-old date palm trees in and around Najran, Saudi Arabia (Althoey et al, 2022a). These trees constitute one of the most accessible diversities and are responsible for a significant volume of agro-waste.…”
Section: Polypropylene Fibres (Ppfs)mentioning
confidence: 99%
“…It has additionally been observed that glass will begin to display pozzolanic behaviors if the diameter is less than 150 microns; moreover, the pozzolanic behaviors will improve if the particle diameter is reduced to less than 35 microns, leading to better outcomes than 150 micron-sized particles [40]. In brief, according to the findings of several researchers, trash may be effectively used as a binding ingredient in concrete [41][42][43] and GW may be reused in concrete without compromising its quality in any way [44], but while also improving the mechanical performance of concrete [45] and enhancing its durability [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research on the strengthening of RC slabs using the TRM, are rather limited in the open literature (Loreto et al, 2014;Koutas and Bournas, 2017;Althoey et al, 2022;Çelik et al, 2022). Loreto et al (2014) studied the behavior of an RC slab with an externally reinforced fabric (PBO) reinforced cementitious matrix layer on the tension face.…”
Section: Introductionmentioning
confidence: 99%